2002
DOI: 10.1557/proc-754-cc9.3
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness of Amorphous Metals and Composites

Abstract: The effects of changes in notch radius on the toughness of two different Zr-based bulk metallic glasses have been determined. It is shown that increases in notch radius produce large increases to the toughness, accompanied by extensive shear banding and crack bifurcation. The fracture toughness of twenty (20) fatigue precracked specimens exhibiting planar crack growth were in the range 20.3 ± 6.7 MPa√m for the two Zr-based glasses. Increasing the notch radius to 110 μm produced notch toughness in the range 95.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…ffiffiffiffi ffi m p of sample "d", which is close to the fracture toughness of the typical ductile Zr-based metallic glasses [47]. With increasing strain rate to the dynamic level, the K C of samples "a" and "b" is nearly the same as those of the quasi-static one.…”
Section: DVsupporting
confidence: 66%
“…ffiffiffiffi ffi m p of sample "d", which is close to the fracture toughness of the typical ductile Zr-based metallic glasses [47]. With increasing strain rate to the dynamic level, the K C of samples "a" and "b" is nearly the same as those of the quasi-static one.…”
Section: DVsupporting
confidence: 66%
“…Toughness values of notched samples of various widths were reported to exhibit higher (2x) fracture toughness values compared to those of fatigue precracked samples [35,36]. The discrepancy in toughness values was partly attributed to the differences in the failure mechanism at the notch root.…”
Section: Journal Of Metallurgymentioning
confidence: 99%
“…Up to now, the investigations of fracture toughness of BMGs are mainly centered on some BMGs with the large GFA, such as Zr-, Pd-, Cu-based BMGs, which makes it easier to utilize unified and conventional methods to measure their fracture toughness.Gilbert et al[372] reported that the monolithic Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5For some other BMGs, which are not adequately tough to produce the pre-cracks, notch toughness is also used to study the toughness of BMGs. Schroers et al[376] showed that Pt-based BMGs (Pt 57.5 Cu 14.7 Ni 5.3 P 22.Wesseling et al[377] reported notch-toughness values in excess of 65 MPa√m by using specimens with a root radius of 110 μm, and the estimated plastic zone size of 63.7 μm is comparable to the order of magnitude of some Zr-based BMGs[373,378]. It is found that the root radius appeared to have insignificant influence on the facture toughness of the brittle Mg 59.5 Cu 22.9 Ag 6.6 Gd 11 BMG[384].Unlike Zr-based glasses, which usually have a large plastic zone, a tiny plastic zone, only about r p = 5 μm, and a few shear bands can be observed ahead of the notch root of 150 μm, corresponding to the low fracture toughness, ~ 10 MPa√m.…”
mentioning
confidence: 99%